Potencialidades energéticas proveniente dos resíduos da mandioca (Manihot Esculenta Crantz) - Silva, Izanilde Barbosa da (2019)
The production of bioethanol from amylaceous biomass from various sources such as cassava has been seen as promising and environmentally sustainable alternatives to replace fossil fuels, as well as the use of waste generated from the processing of these. Considering the large production of agroindustrial materials from the cassava crop with one of the largest national productions, and the current search for the use of renewable energy sources, together with the need for information on the fuel material for the development of conversion technologies of agro-industrial waste, in biofuels. The main objective of this research is the residual use of manioc for energy generation. The residues analyzed came from two agroindustries located in the city of Pedra de Fogo-PB and two types of residues were collected and selected: solid (bark) and liquid (manipueira). Monthly waste generated in the two agroindustries is 12.43 tons of bark in one month and 10,916 liters of manure. The characterizations had significant results. In the humidity tests 93.03% for the manipueira and 88.5 for the bark, calorific value of 16.22 MJ / kg, the ashes 0.8 for manipueira and 1.6 for the barks. In the alcoholic fermentation, the best conditions for ethanol production in the present study were: M2 and M4 inoculated culture media with reductive sugars 35.7 g.L-1 and 26 g.L-1 and for culture medium with addition of molasses The result of reducing sugars was 57.4 g.L-1 . , the alcohol content of the wine was found for the M2, M4 and M5 cultures, the values of 2.2 ºGL, 2.5 ºGL and 5.9 ºGL respectively. The results indicate that cassava residues have important characteristics and potential for the production of biofuels. This study has as final product experimental data on the use of industrial waste, aiming at the generation of clean and renewable energy and increasingly attractive in the world, considering the growing environmental and economic concern.